POLA KOMUNIKASI KEPALA MADRASAH DALAM PENGEMBANGAN KARIR GURU DI MIS AL-AFKARI - Amiruddin Siahaan; Ismail Ismail; Ibnu Hajar; Hera Herviana; Muhammad Walimsyah Sitorus (Jurnal Guru Kita PGSD, 2021)
Abstract: The Head of Madrasah Communication Patterns in Teacher Career Development at Mis Al-Afkari. Communication is very important in educational organizations to convey messages, without communication or lack of communication within the organization it will hinder the progress of an organization, especially education. This paper aims to determine the communication pattern of the madrasa principal in developing teacher careers at MIS Al-Afkari. Qualitative research with case study method was chosen in this paper to reveal data by using data collection techniques through interviews, observation and documentation. Based on this research, it was found that, 1) The head of the MIS Al-Afkari madrasa builds good and effective communication with teachers in developing teacher careers, 2) The head of the MIS Al-Afkari madrasa provides opportunities openly to all MIS Al-Afkari teachers. in terms of career development, 3) The head of the MIS Al-Afkari madrasa communicates the achievement of madrasa goals to all components, especially teachers at MIS Al-Afkari properly and effectively through the madrasa principal's working meeting forum with teachers. In general, it can be concluded that the communication carried out by the head of Madrasah is good and effective in terms of career development of teachers at MIS Al-Aflkari. Keywords: Communication Pattern, Career Development Abstrak: Pola Komunikasi Kepala Madrasah Dalam Pengembangan Karir Guru Di Mis Al-Afkari. Komunikasi merupakan hal yang sangat penting di dalam organisasi pendidikan untuk meyampaikan pesan-pesan, tanpa komunikasi atau minimnya komunikasi dalam organisasi maka akan menghambat kemajuan sebuah organisasi terutama pendidikan. Tulisan ini bertujuan mengetahui pola komunikasi kepala madrasah dalam pengembangan karir guru di MIS Al-Afkari. Penelitian kualitatif dengan metode studi kasus dipilih dalam tulisan ini untuk mengungkap data dengan menggunakan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Berdasarkan penelitian ini ditemukan bahwa, 1) Kepala madrasah MIS Al-Afkari membangun komunikasi yang baik dan efektif kepada guru-guru dalam penegembangan karir guru, 2) Kepala madrasah MIS Al-Afkari memberikan kesempatan secara terbuka kepada seluruh guru-guru MIS Al-Afkari dalam hal pengembangan karir, 3) Kepala madrasah MIS Al-Afkari mengkomunikasikan pencapaian tujuan-tujuan madrasah kepada seluruh komponen khususnya guru di MIS Al-Afkari dengan baik dan efektif melalui forum rapat kerja kepala madrah dengan guru. Secara umum dapat disimpulkan bahwa komunikasi yang dilakukan oleh kepala Madrasah sudah baik dan efektif dalam hal pengembangan karir guru-guru di MIS Al-Aflkari.  Kata Kunci: Pola Komunikasi, Pengembangan Karir